Analysis of the Institutional Position of Military Judges Against the Independence of the Indonesian Military Courts - Irwan Sanjaya Putra; Niken Wahyuning Retno Mumpuni (Nurani Hukum, 2022)
Application of a theory of power-sharing which is divided into executive, legislative, and judicial branches in Indonesia has been applied to achieve checks and balances between state institutions. The judiciary must stand upright in carrying out its primary duties and functions as a law enforcement agency. In the context of military justice, judges have an undeniably important role in the running of a judicial body. The position of military judges has ties between two institutions, namely the Indonesian National Armed Forces (executive) and the Supreme Court (judicial) which should be of different clumps. Judicial bodies that should be independent, uninterrupted, and intervening must be reviewed from the perspective of laws and regulations. This research uses the normative-empirical method (applied law research). The approach in question is in the form of a conceptual approach by examining the structure of the state administrative organization based on applying a theory and legislation and their implementation in the field. Military judges indirectly stand on two legs institutionally, because both the Supreme Court and the TNI have the same role in determining the career path of military judges. In that case, military judges still have great potential for intervention. Several factors affect the independence of military judges in carrying out their duties within the scope of military justice. Military judges indirectly stand on two legs institutionally, because both the Supreme Court and the TNI have the same role in determining the career path of military judges. In this regard, the military courts in Indonesia are not yet fully considered an independent judiciary. This is because several factors that have great potential in determining a judge can be intervened by another party (executive).